ALOKASI DANA DESA TERHADAP PEMBANGUNAN DESA TRAPANG BANYUATES SAMPANG PERSPEKTIF PEMBANGUNAN IBNU KHALDUN - Mailadatul Mufallihah (STAI Nurul Qadim, 2025)
The management of village funds in the scope of community economic development is part of efforts to prosper the village in accordance with the purpose of allocating village funds. This study aims to determine the allocation of village funds for the development of the village of Trapang Banyuates Sampang from the development perspective of Ibnu Khaldun. The type of research used is descriptive qualitative research with interview data collection techniques, observation. The effectiveness of managing village funds is illustrated by aspects of planning, implementation, supervision and accountability with the results that the village government has allocated village funds properly but has not been optimal in mapping village programs. The development of Trapang Village, in Ibnu Khaldun's view, is still not optimal, especially in infrastructure development and increasing human resources which are not yet efficient. The village government is also not optimal in mapping village needs and the inclusion of community participation in making decisions is very minimal.